Peran Persepsi Akuntansi Keuangan dan Pemasaran dalam Membentuk Persepsi Nilai Perusahaan di Kalangan Mahasiswa - Deti Susilawati; Fuadi Fuadi; Evi Dora Sembiring; Sari Putri Pertiwi; Ade Samsinar (ARBITRASE: Journal of Economics and Accounting, 2026)
This research aims to analyze the role of perceptions of financial accounting and marketing in shaping perceptions of company value among students. The research problem is based on the importance of students' understanding of various business functions in assessing company value comprehensively. This research uses a quantitative approach with a survey method of students as respondents. Data was collected through questionnaires and analyzed using multiple linear regression to partially test the influence of each variable. The novelty of this research lies in the use of student perceptions as a unit of analysis in studying the formation of company value, which is generally researched at the company or investor level. The research results show that perceptions of financial accounting and perceptions of marketing have a positive and significant effect on perceptions of company value, with perceptions of marketing having a more dominant influence. These findings indicate that company value is not only perceived from the aspect of financial performance, but is also influenced by the role of marketing in creating value. This research provides a theoretical contribution in expanding the study of corporate value formation from an individual perspective as well as a practical contribution for universities in designing learning that is more relevant to the needs of the business world.